The Development of Writing Folk Poetry Teaching Material According to the Materials Expert Team with Copy the Master Technique for Seventh Grade Student of Junior High School 1 Rantau Selatan, In Labuhan Batu District, Indonesia - Tetty Matanari; Syahnan Daulay; Malan Lubis (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The development of a teaching material must be based on the analysis of student needs. Development of teaching materials have to be able to answer or solve problems or difficulties in learning. This study aims to know the development of writing folk poetry teaching material according to the materials expert team with copy the master technique for seventh grade student of junior high school 1 Rantau Selatan, in Labuhan Batu District. This study was conducted by using Probability Sampling technique. The result shows that all teachers and students need modules in the learning process. Teaching material products developed in folk poetry writing materials with copy the master learning technique for seventh grade students of junior high school 1 Rantau Selatan meet the requirements and are appropriate to use based on the validation of material experts and design experts.